About fractional integro-differentiating the trigonometric functions - Денисюк, В. П.; Рибачук, Л. В. (Problems of Informatization and Control, 2008)
The comparison of fractional derivatives and integrals of trigonometric functions, calculated with the use of methods proposed by Liuvil, Riman-Liuvil, Adamar and Weyl is considered: some numerical results of these methods comparison is presented